Predictors of Smartphone and Tablet Use Among Patients With Hypertension: Secondary Analysis of Health Information National Trends Survey Data - Chinwe E Eze; Brady T West; Michael P Dorsch; Antoinette B Coe; Corey A Lester; Lorraine R Buis; Karen Farris (JMIR Publications, 2022)
BackgroundUncontrolled hypertension leads to significant morbidity and mortality. The use of mobile health technology, such as smartphones, for remote blood pressure (BP) monitoring has improved BP control. An increase in BP control is more significant when patients can remotely communicate with their health care providers through technologies and receive feedback. Little is known about the predictors of remote BP monitoring among hypertensive populations. ObjectiveThe objective of this study is to quantify the predictors of smartphone and tablet use in achieving health goals and communicating with health care providers via SMS text messaging among hypertensive patients in the United States. MethodsThis study was a cross-sectional, secondary analysis of the 2017 and 2018 Health Information National Trends Survey 5, cycles 1 and 2 data. A total of 3045 respondents answered "Yes" to the question "Has a doctor or other healthcare provider ever told you that you had high blood pressure or hypertension?", which defined the subpopulation used in this study. We applied the Health Information National Trends Survey full sample weight to calculate the population estimates and 50 replicate weights to calculate the SEs of the estimates. We used design-adjusted descriptive statistics to describe the characteristics of respondents who are hypertensive based on relevant survey items. Design-adjusted multivariable logistic regression models were fitted to estimate predictors of achieving health goals with the help of smartphone or tablet and sending or receiving an SMS text message to or from a health care provider in the last 12 months. ResultsAn estimated 36.9%, SE 0.9% (183,285,150/497,278,883) of the weighted adult population in the United States had hypertension. The mean age of the hypertensive population was 58.3 (SE 0.48) years. Electronic communication with the doctor or doctor's office through email or internet (odds ratio 2.93, 95% CI 1.85-4.63; P<.001) and having a wellness app (odds ratio 1.82, 95% CI 1.16-2.86; P=.02) were significant predictors of using SMS text message communication with a health care professional, adjusting for other demographic and technology-related variables. The odds of achieving health-related goals with the help of a tablet or smartphone declined significantly with older age (P<.001) and ownership of basic cellphones (P=.04). However, they increased significantly with being a woman (P=.045) or with being married (P=.03), having a wellness app (P<.001), using devices other than smartphones or tablets to monitor health (P=.008), making health treatment decisions (P=.048), and discussing with a provider (P=.02) with the help of a tablet or smartphone. ConclusionsIntervention measures accounting for age, gender, marital status, and the patient's technology-related health behaviors are required to increase smartphone and tablet use in self-care and SMS text message communication with health care providers.